Pengaruh Pengetahuan dan Pengalaman terhadap Minat Menjadi Auditor Internal dengan Dukungan Orang Tua sebagai Variabel Moderasi: (Studi Kasus Mahasiswa Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya) - Carissa Diastri Nari Ratih; Ambar Kusumaningsih (STIKes Ibnu Sina Ajibarang, 2025)
Internal audit is an assessment function that has been developed independently of an organization in assessing and testing activities that support services to business organizations. Internal audit carries out objective evaluations within the organization, overseeing the functions of accounting, finance, and various other areas as the basis for administrative services. This research aims to examine the influence of knowledge, experience and parental support on students' interest in becoming internal auditors. The variables used in this research are knowledge and experience as independent variables, parental support as a moderating variable and interest in becoming an internal auditor as the dependent variable. The data used in this research was collected using a questionnaire method distributed to accounting students class of 2020 who had completed internal audit courses and carried out practical field work. A total of 89 respondents were the result of the data from the number of samples that were successfully processed. Probability sampling method with purposive sampling technique used. The analysis techniques in this research are multiple linear regression analysis and moderated regression analysis (MRA). The results of this research show that knowledge and experience directly influence interest in becoming an internal auditor and parental support is able to moderate knowledge and experience in students' interest in becoming an internal auditor.